If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(3x + -17) = 52 Reorder the terms: 8x + -1(-17 + 3x) = 52 8x + (-17 * -1 + 3x * -1) = 52 8x + (17 + -3x) = 52 Reorder the terms: 17 + 8x + -3x = 52 Combine like terms: 8x + -3x = 5x 17 + 5x = 52 Solving 17 + 5x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 5x = 52 + -17 Combine like terms: 17 + -17 = 0 0 + 5x = 52 + -17 5x = 52 + -17 Combine like terms: 52 + -17 = 35 5x = 35 Divide each side by '5'. x = 7 Simplifying x = 7
| 5y+2x=19 | | -2x+2=-7+17 | | 15-(-30s)=465 | | 3(x-1)4+7=19 | | 2s-3=9 | | Y=ln(1-x^2) | | Y=(18-9)*p | | x=23+9 | | 3=16x+15 | | 17-2(1-3x)4=5 | | h(-3)=-3 | | 8(-3n-7)+6(6+4n)=-24 | | -9h+32=-67 | | 5-m=131 | | 11x^2=5x-3 | | 16+3x=7x-3 | | 4x^3+5x^2+2x+16=X+2 | | 10x+15+6x-11=180 | | 3x^2+5x=16 | | 4x^3+5x^2+2x+16= | | 3x*2+5x=16 | | 36=-3(k-6) | | y=-0.05x^2+1.25x | | 3(2x+9)=-15 | | 3(w-11)=15 | | 18z-17z+3=17 | | 10-2r=6 | | -6.8(2p+5)-1.6(4p+6)= | | T=24m-4m^2 | | 16=4(n+1) | | h(-4)=-5 | | ix^2-8x+30=0 |